A new look at energy harvesting half-duplex DF power splitting protocol relay network over rician channel in case of maximizing capacity - Phu Tran Tin; Minh Tran; Tan N. Nguyen; Thanh-Long Nguyen (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, the system performance in term of the ergodic capacity of a half-duplex decode-and-forward relaying network over Rician Fading Channel is investigated. The power splitting protocol is proposed for the system model. For this purpose, the analytical mathematical expressions of the ergodic capacity in cases of maximize and no-maximize ergodic capacity are derived and discussed. Furthermore, the effect of various system parameters on the system performance is rigorously studied. Finally, the analytical results are also demonstrated by Monte-Carlo simulation in comparison with the analytical expressions. The research results show that the analytical mathematical and simulated results match for all possible parameter values for both schemes.